Al-Qur’an dan Rekonstruksi Worldview Keagamaan: Fondasi Holistik dalam Pendidikan Islam - Kurnia, Neneng (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study aims to examine how the Qur'an can serve as a foundation for the reconstruction of religious worldview in Islamic education. The issue addressed is how Islamic education can integrate Qur'anic values to form a holistic worldview that encompasses not only spiritual aspects but also social, moral, and intellectual dimensions. The purpose of this research is to explore the concept of worldview in the Qur'an and its application in the context of Islamic education. The research method used is a literature study with a qualitative approach, examining Qur'anic texts and works of scholars discussing the relationship between religious worldview and education. The findings indicate that the Qur'an offers a comprehensive worldview that covers personal, social, and spiritual aspects of life. The reconstruction of a religious worldview in Islamic education based on the Qur'an can shape individuals with a balance between knowledge, ethics, and spirituality. By integrating Qur'anic teachings into education, students can form a more holistic perspective on the world and life. In conclusion, the Qur'an holds significant potential as a foundation for constructing a holistic religious worldview in Islamic education, which can equip students with a profound understanding of their role in this world and the hereafter. The implications of this study suggest the importance of applying Qur'anic teachings in Islamic education curricula to create more balanced and responsible individuals.